Value Stream Analysis and Middlemen Impact of Skipjack Tuna and Smoothbelly Sardinella Dried Fish Value Chains in Sri Lanka - Wickrama, Shalika Laksan; Koralagama, Dilanthi; Abeysinghe , Sandika (Advances in Technology, 2022)
Value-added activities, chain structures, and middlemen impact are incomprehensible in the dried fish economy. Processors have a significant impact at the initial stage of the value chain, but little control over value chain management; however vastly monopolized by intermediaries. Yet, the processors receive poor returns compared to other actors in the value chain. Value stream analysis visualizes the value additions incorporated by all the actors and agents in the value chain. Despite the literature states of different returns along the value chain, a comprehensive mapping is needed to assess the contribution by actors and agents over Value Added (VA), Necessary Value Added (NVA) and Non-Necessary Value Added activities (NNVA). This will enable fair and efficient functions in the value chain. The same scenario is common in dried fish value chains in Sri Lanka which is inadequately researched. This study aims to conduct a value stream analysis, middlemen impact assessment, and their relationship for skipjack tuna and smoothbelly sardinella dried fish value chains representing the highest per-capita consumption dried fish varieties in Sri Lanka. Hambantota, Matara, Puttalam, and Gampaha were selected to conduct the study representing the highest dried fish production districts. A quantitative data collection method was adopted employing a pre-tested structured questionnaire. A simple random sampling technique was used to draw the sample from processors, wholesalers and retailers where the sample sizes were 100, ,40, and 40 respectively. Secondary data were collected from reputed published materials. Data were analyzed mainly using descriptive techniques. The number of VA, NV,A and NNVA activities are approximately decreased through the skipjack tuna value chain as processor (VA-10, NVA-01, NNVA-02), wholesaler (VA-2, NVA-1, NNVA-4) and retailer (VA-02, NVA-01, NNVA-01) and for smoothbelly sardinella processor (VA-08, NVA-01, NNVA-02), wholesaler (VA-02, NVA-01, NNVA-02) and retailer (VA-01, NVA-01, NNVA-02) levels. Time spent for each activity is decreased through value chain for both dried fish varieties. The market margins for skipjack tuna and smoothbelly sardinella are 46.64% and 38.19% respectively. Profit margins are increased along the value chain at the processor, wholesaler and retailer levels for skipjack tuna (9.63%, 15.25%, 27.22%) and smoothbelly sardinella (12.53%, 14.23%, 20.98%) respectively. In contrast, profit gain was not fairly distributed along the value chain proportionately contribution to activities and times spent by actors. This recommended an effective mechanism for fair profit sharing for dried fish actors based on their contribution to value addition and time spent on each activity.